Comparative characterization study of LYSO:Ce crystals for timing applications. (1st August 2022) - Addesa, F.M.; Barria, P.; Bianco, R.; Campana, M.; Cavallari, F.; Cemmi, A.; Cipriani, M.; Dafinei, I.; D'Orsi, B.; del Re, D.; Diemoz, M.; D'Imperio, G.; et al.
Abstract: Cerium-doped Lutetium-Yttrium Oxyorthosilicate (LYSO:Ce) is one of the most widely used Cerium-doped Lutetium based scintillation crystals. Initially developed for medical detectors it rapidly became attractive for High Energy Particle Physics (HEP) applications, especially in the frame of high luminosity particle colliders. In this paper, a comprehensive and systematic study of LYSO:Ce ([Lu(1- x ) Y x ]2 SiO5 :Ce) crystals is presented. It involves for the first time a large number of crystal samples (180) of the same size from a dozen of producers. The study consists of a comparative characterization of LYSO:Ce crystal products available on the market by mechanical, optical and scintillation measurements and aims specifically, to investigate key parameters of timing applications for HEP.